Multi-Element Synthetic Transmit Aperture in Medical Ultrasound Imaging - TROTS, Ihor; NOWICKI, Andrzej; LEWANDOWSKI, Marcin; TASINKEVYCH, Yuriy (Archives of Acoustics, 2013)
Synthetic aperture (SA) technique is a novel approach to present day commercial systems and has previously not been used in medical ultrasound imaging. The basic idea of SA is to combine information acquired simultaneously from all directions over a number of emissions and to reconstruct the full image from these data.The paper presents the multi-element STA (MSTA) method for medical ultrasound imaging. The main difference with the STA approach is the use of a few elements in the transmit mode in contrast to a single element aperture. This allows increasing the system frame rate, decreasing the number of emissions, and provides the best compromise between the penetration depth and lateral resolution. Besides, a modified MSTA is proposed with a corresponding RF signal correction in the receive mode, which accounts for the element directivity property.In the experiments a 32-element linear transducer array with 0.48 mm inter-element spacing and a burst pulse of 100 ns duration were used. Two elements wide transmission aperture was used to generate an ultrasound wave covering the full image region. The comparison of 2D ultrasound images of a tissue mimicking phantom obtained using the STA and MSTA methods is presented to demonstrate the benefits of the second one.